Is TCR effective in reducing tax avoidance in Indonesia? - Hendrastuti, Ranindya; Sukoharsono, Eko Ganis; Iqbal, Syaiful (The Indonesian Accounting Review, 2024)
Thin capitalization is a tax avoidance technique using funding sources that prioritize debt over capital. Thin capitalization can be used as a technique to avoid taxes because there is a difference in treatment between debt and capital as a source of funding in tax regulations. Thin capitalization rule (TCR) is domestic tax system to reduce thin capitalization. This study aims to examine the effect of implementing thin capitalization rules on reducing tax avoidance in Indonesia. This study is a quantitative study. The data used are secondary data obtained from multinational companies listed on the IDX from 2013 to 2020 by excluding companies that are excluded from PMK-169: bank companies, financing institutions, insurance, reinsurance, operating in the oil and gas mining sector, companies whose entire income is subject to final tax, and infrastructure. The data analysis method used in this study is regression using the eviews 12.0 program. The results show that the implementation of thin capitalization rule (TCR) does not reduce tax avoidance. These results provide empirical evidence that the government need to consider using thin capitalization rule with the interest to Earnings Before Interest, Tax, Depreciation, and Amortization (EBITDA) rule mechanism rather than the Debt-to-Equity Ratio (DER) rule mechanism and arm’s length rule mechanism.